Long-term impact of changing childhood malnutrition on rotavirus diarrhoea: Two decades of adjusted association with climate and socio-demographic factors from urban Bangladesh. - Sumon Kumar Das; Mohammod Jobayer Chisti; Mohammad Habibur Rahman Sarker; Jui Das; Shawnawaz Ahmed; K M Shahunja; Shamsun Nahar; Nora Gibbons; Tahmeed Ahmed; Abu Syed Golam Faruque; Mustafizur Rahman; George J Fuchs; et al. (PLoS ONE, 2017)
Background There is strong association between childhood rotavirus, diarrhoea, climate factors and malnutrition. Conversely, a significant nutritional transition (reduced under-nutrition) with a concurrent increasing trend of rotavirus infection in last decade was also observed among under 5 children, especially in developing countries including Bangladesh. Considering the pathophysiology of rotavirus, there might be an interaction of this nutrition transition which plays a pivotal role in increasing rotavirus infection in addition to climate and other man-made factors in urban areas such as Dhaka, Bangladesh. Methods Relevant monthly data from 1993-2012 were extracted from the archive of the Diarrhoeal Disease Surveillance System of icddr, b and linked with data collected from the Dhaka station of the Bangladesh Meteorological Department (mean temperature, rainfall, sea level pressure and humidity). Seasonal autoregressive integrated moving average time series models were deployed to determine the association between the monthly proportion of rotavirus infection and underweight, stunting and wasting adjusting for climate, socio-demographic and sanitation factors. Finding The proportion of rotavirus cases among all causes diarrhoea increased from 20% in 1993 to 43% in 2012 (Chi squared for trend p = 0.010). In contrast, underweight, stunting and wasting decreased from 59%-29% (p<0.001); 53%-21% (p<0.001) and 32%-22% (p<0.001) respectively over the same period. Mean ambient temperature increased from 25.76°C-26.62°C (p = 0.07); mean rainfall, sea level pressure and mean humidity decreased from 234.92-111.75 mm (p = 0.5), 1008.30-1006.61 mm of hg (p = 0.02) and 76.63%-70.26% (p<0.001), respectively. In the adjusted model, a decrease in monthly proportion of underweight [coef.: -0.189 (95% CI:-0.376, -0.003)] and wasting [-0.265 (-0.455, -0.075)] were significantly and inversely associated with rotavirus infection. However, an inverse but insignificant association was observed for stunting [-0.070 (-0.249, 0.109)]. Interpretation The reduction of acute childhood malnutrition is significantly associated with increasing rotavirus diarrhoea among under-5 children. Thus mass vaccination in addition to interventions directed at man-made modifiable predictors for prevention and control is warranted.